Devletlerarası İlişkilerde Kurumsallaşma Örneği Olarak Şanghay İşbirliği Örgütü - Tamer KAŞIKCI (Gazi Akademik Bakış)
After the Second World War, in order not to experience the great wars that shook the fundamental basement of international relations and disrupted the political, economic and cultural relations between states and to ensure the continuity of these relations, multilateral institutional arrangements were established. However, while the effort to institutionalize inter-state relations with these regulations had been reached a higher level of institutionalization in Western societies where permanent and effective organizations such as the EU and NATO were produced, they did not have similar levels in the rest of the world. The study, which focuses on this fundamental problem, examines the state of institutionalization activities in the Asian region through the Shanghai Cooperation Organization. In this context, in the study, it is argued that the SCO, as in other institutionalization activities in Asia, did not reach a strong level of institutionalization due to the problems experienced in elements such as leadership, common interest and common identity.